Illustration as a Teaching-Learning Tool in Histology Practical in Undergraduate Medical Education of Bangladesh: Teacher & Student Perspective - Ahmed, Rukshana; Shamim, Khondoker Manzare; Talukder, Humayun Kabir (Bangladesh Journal of Anatomy, 2024)
Objectives: This study was aimed to find out the perception of students and teachers regarding illustration as a teaching-learning tool in pistology practical class in undergraduate medical education of Bangladesh. Methods: The present study was a cross sectional descriptive one involving quantitative and qualitative methods. Data was collected from 10 medical colleges. 824 1st year MBBS students were enrolled in the survey. A semi-structured questionnaire having multiple response answers was used for obtaining information from the students and in-depth interviews were carried out with 21 teachers of Anatomy. Results: Students mentioned that use of illustration is interesting and helpful for proper understanding of histological structure. A majority of the respondents (66%) mentioned “schematic diagram as their choice of form of illustrations. The interviewee teachers agreed that illustration is very much useful for histology practical session. Conclusions: Illustration aids in better recognition of histological structure. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 1, pp. 3-7